Tax planning of married couples in East and West Germany - Katharina Erbe (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
This study evaluates the tax planning behavior of married couples with regard to the allocation of tax schedules between spouses in the context of the German income tax splitting. The focus lies on the disparities between East and West German couples since they experienced different political regimes until 1990. The analysis utilizes administrative data on German income tax returns for the year 2004 (FAST 2004). The result of an alternative specific conditional logit estimation indicates that East German couples are substantially more likely to choose equal tax schedules than West Germans (between 17.8 and 19.3 percentage points). East German couples are less likely to allocate the advantageous tax bracket to the husband instead of the wife, even when controlling for income and socioeconomic factors. The conclusion of this analysis is that the tax planning behavior of married couples is influenced by the differences in the socialization of people, caused by the fact that before 1990, East Germany had different tax institutions and political regimes compared to West Germany.
Keywords: H24; H31; 330; Income Tax Splitting; Household Decision; East and West Germany